PolyJet-Printed Bellows Actuators: Design, Structural Optimization, and Experimental Investigation - Dämmer, Gabriel; Gablenz, Sven; Hildebrandt, Alexander; Major, Zoltan (Frontiers in Robotics and AI, 2019)
Abstract—Pneumatic bellows actuators are exceptionally suitable for Additive Manufacturing (AM) as the required geometrical complexity can easily be obtained and their functionality is not affected by rough surfaces and small dimensional accuracy. This paper is an extended version of a previously published contribution to the RoboSoft2018 conference in Livorno, Italy. The original paper [1] contains a simulation-driven design approach as well as experimental investigations of the structural and fatigue behavior of pneumatic multi-material PolyJetTM bellows actuators. This extended version is enhanced with investigations on the relaxation behavior of PolyJet bellows actuators. The presented results are useful for researchers and engineers considering the application of PolyJet bellows actuators for pneumatic robots.